2020
DOI: 10.3390/catal10121455
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Amorphous Molybdenum Sulfide (MoSx)/CdIn2S4 Composite Photocatalyst: Co-Catalyst Using in the Hydrogen Evolution Reaction

Abstract: Co-catalyst deposition is used to improve the surface and electrical properties of photocatalysts. In this work, MoSx/CdIn2S4 nanocomposites were prepared by a facile hydrothermal and photodeposition route. The basic crystalline phases and morphology of the as-prepared samples were determined, and these results showed that MoSx was tightly anchored onto CdIn2S4 by sharing the same S atom. In the hydrogen production experiments, MoSx/CdIn2S4-40 displayed the optimal photocatalytic hydrogen production yield in 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…The peak of binding energy of 228.9 eV is Mo 4+ 3d 5/2 (Figure c). The three peaks of S 2p 3/2 , S 2p 1/2 and S 2p appear at 161.6 eV, 162.7, and 167.9 eV (Figure d), corresponding to S 2p in S compounds. ,, The weak peak at 163.1 eV indicates that unsaturated S atoms existed in the sample. The S atom in the sample exists in the form of S 2– and S2- 2, which is consistent with the reported results of MoS x . …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The peak of binding energy of 228.9 eV is Mo 4+ 3d 5/2 (Figure c). The three peaks of S 2p 3/2 , S 2p 1/2 and S 2p appear at 161.6 eV, 162.7, and 167.9 eV (Figure d), corresponding to S 2p in S compounds. ,, The weak peak at 163.1 eV indicates that unsaturated S atoms existed in the sample. The S atom in the sample exists in the form of S 2– and S2- 2, which is consistent with the reported results of MoS x . …”
Section: Resultssupporting
confidence: 90%
“…49 The amorphous MoS x with uneven organization and long-range disturbed layer is rich in unsaturated sulfur atoms, which can adsorb and activate inert N 2 molecules. 50 Meanwhile, MoS x also has excellent light absorption and photothermal properties. In the present work, the CuO/CM substrate was prepared by chemical oxidation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photocatalytic H 2 evolution reaction was operated in a typical reaction system according to our previous reports [ 40 , 41 , 42 ]. The photocatalytic experiment was carried out under visible light (λ ≥ 420 nm).…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, coupling CdIn 2 S 4 with other materials with metallic or semiconducting properties in forming heterostructures has been conducive to overcoming the aforementioned limitations. Recently, Li et al explored the pertinent construction of amorphous MoS x with CdIn 2 S 4 in forming a metal–semiconductor Schottky junction. The study suggested that MoS x is a potential cocatalyst candidate for a metal substituent owing to its abundant active centers associated with unsaturated atoms in catalyzing the HER .…”
Section: Recent Advances In Indium-based Ternary Metal Sulfidesmentioning
confidence: 99%